Prevalence of vertebral fractures and serum sclerostin levels in acromegaly - YAVUZ, DİLEK; BUĞDAYCI, ONUR (SPRINGER, 2021)
Objective An increased prevalence of vertebral fractures (VFs) has been reported in previous studies. The aim of this study was to evaluate the association between bone mineral density (BMD), bone turnover markers, serum sclerostin levels, and vertebral fractures (VFs) in acromegaly patients. We also evaluated the effects of gonadal status, disease activity, treatment modality, age, sex, and body mass index (BMI) on skeletal endpoints. Design Case-control study. Patients and measurements Seventy acromegaly patients (M/F:36/34, mean age 45.5 +/- 11.9 years) and 70 controls (M/F:31/39; mean age 45.66 +/- 11.9 years) were included. VFs, BMD, calcium metabolism, markers of bone turnover, and sclerostin levels were evaluated. BMD was measured by dual-energy X-ray absorptiometry (Hologic QDR 4500). Conventional lateral radiography of the spine was performed and the Genant method was used for the assessment of fractures of T4-L5 vertebrae. Results The prevalence of vertebral fractures was higher in acromegalic patients as compared with the control group (72.9 vs. 20%; p < 0.001). Serum phosphate (P) levels (3.46 +/- 0.59 mg/dl vs. 3.11 +/- 0.44 mg/dl; p < 0.001) and b-cross laps (CTx) levels (0.47 mu g/l, range 0.04-2.38 vs. 0.28 mu g/l, range 0.11-0.80; p < 0.001) were significantly higher in acromegaly patients than control subjects. Serum sclerostin levels were similar between either acromegaly patients and control subjects or acromegaly patients with VF and without VF. In the means of treatment modality, VFs were more frequent in patients treated with adjuvant gamma knife radiosurgery (GKS) (p = 0.07). In the binary logistic regression analysis, the age of the acromegaly patients, the presence of hypogonadism, and GKS treatment were the factors significantly correlated with the occurrence of spinal fractures. Conclusions The prevalence of VFs in patients with acromegaly is higher than in control subjects. Since advanced age, the presence of hypogonadism and GKS treatment were the factors predicting VFs in acromegaly; radiological evaluations should be considered as an emerging tool especially in those patients. Although markers of bone turnover elevated in acromegaly, they were not useful for the prediction of fractures. Serum sclerostin levels showed no discrepancy between the two groups and further studies are required for assessment of sclerostin role in this form of secondary osteoporosis.
Keywords: Acromegaly; Bone turnover markers; Vertebral fracture; Sclerostin; Hypogonadism; Radiosurgery; BONE-MINERAL DENSITY